Síntese de magnetos moleculares à base de ligantes derivados de fenilenobis(oxamato) via estratégia metalosupramolecular - Tatiana Renata Gomes Simoes (2014)
In this work, low and high dimensional molecular magnets were synthesized and characterized and their magnetic properties were investigated. Initially, reactions involving the precursor bis(2-pyridylcarbonyl) amidete of copper (II) [Cu(bpca)(H2O)2]+,and its influence on species containing the ortho-phenylenebis(oxamate) group (opba) were investigated. Four compounds were obtained and characterized, being the X-ray structure of two of them determinated for the first time [Cu(bpca)(CF3SO3)(H2O)]·H2O and the chain {[Cu(bpca)(EtHopba)]}n . The magnetic study of {[Cu(bpca)]2[Cu(opba)(H2O)]}, [Cu2(bpca)2(H2opba)]2·3H2O and{[Cu(bpca)(EtHopba)]}n showed antiferromagnetic coupling between the paramagnetic centers with J = -65.8, -2.36 and -0.17 cm-1, respectively. Afterwards, it was prepared a new spin-canted heterobimetallic 2-D network of formula (Bu4N)[Mn2{Cu(opba)}2ox], representing a unique example of a layered system containing copper(II) andmanganese(II) ions bridged by oxamate and oxalate groups. The intralayer antiferromagnetic interactions in the complex spin topology were evaluated through the analysis of the magnetic susceptibility data by the use of the QMC methodology which best-fit data was JCuMn = 32.5(3) cm1, e JMnMn = 2.7(3) cm1. On the third partof this work three novel dinuclear compounds with the chemical formula[Cu(opba)Cu(phen)(dmso)2].2H2O, [Cu(opba)Cu(dap)(H2O)].H2O and[Cu(opba)Cu(dap-OH)(H2O)].2H2O with phen = 1,10 phenanthroline, dap = 1,3 diaminopropane and dap-OH = 2-hidroxi-1,3 diaminopropane have been synthesized and their crystal structures have been determined. The fiting of magnetic data revealed a strong antiferromagnetic coupling among the metal centers throughthe oxamate bridge with J = -358.8, -366.0 e -392.1 cm-1 respectively. Finally, it was studied the solvent-driven preparation and structural characterization of the dinuclear compound [Cu(bipy)(H2mpba)]2·2H2O and the neutral chain [Cu(bipy)(H2mpba)]·dmso [bipy = 2,2'-bipyridine and H4mpba = N,N'-1,3-phenylenebis(oxamic acid)]. Thereversible interconversion between them is also presented and the magnetic studies reveals weak intradinuclear (J = -0.81 cm-1) and intrachain magnetic interactions (J = - 0.22 cm-1).